Analysis of down time and reliability estimation in hostel building maintenance - A case study - Ab Wahab, Yuseni; Hasan Basari, Abd Samad (IDOSI, 2013)
The growths of present Hostel Building Maintenance (HBM) are forced towards the use of more complex systems. In consequences, with the increase in automation and usage of complex systems, evaluation of reliability has recently been recognized for effective maintenance. Reliability has been evaluated mostly for civil, electrical and chemical components and presently we are going to calculate reliability for components in a Hostel Building. For this purpose, the breakdown time is calculated from the Hostel Building of Higher Education Institution in Malacca, Malaysia. The data is analyzed and the reliability is calculated for each component by exponent distribution in probability. Reliability is analyzed and criticality of each component is found by using FMEA (Failure Mode and Effect Analysis) to suggest an appropriate preventive maintenance schedules. The study was carried in the Hostel Building at Kolej Universiti Islam Melaka (KUIM) with the capacity of 5300 students per semester. The preliminary discussions with the officer's in charged reveals that the hostel buildings are often create problems due to breakdown of various components. Hence, it is decided to carry out failure analysis and to suggest measures to improve the availability of the components. The objective of this study is to estimate availability, reliability of the component system and also to perform the FMEA analysis to identify the critical components to “prepare Preventive Maintenance (PM) schedules”. The methodology that has been followed to achieve this study is starting with the collection of the historical failure data of the hostel building. Then, the down time and the availability of the equipment is calculated based from the past data. Once finished the failure history is modeled using exponent distribution. After that, the reliability of the components is estimated using exponent parameters and finally calculating criticality index of all the components using FMEA software. It is possible to correlate the equipment reliability with maintenance requirements. In order to attain maximum productivity, it is necessary to optimize man inducement in minimizing failure. This can be achieved by applying a proper maintenance and timely replacement of some parts of components or at times the whole equipment’s. An attempt has been made in this work to study the failure pattern and down time of the components. The critical components are also identified by carrying FMEA Analysis.